Предмет: Алгебра, автор: vserebrova108

При у=60,Пожалуйста ​

Приложения:

Ответы

Автор ответа: DocAlfer
1

Ответ:

Объяснение:

... = \frac{(y-4)^{2} }{(y-4)(y+4)} * \frac{y(y+4)}{10(y-4)}  = \frac{y}{10}  = \frac{60}{10} = 6


vserebrova108: Спасибо
Автор ответа: Sashaznaet05
2

Ответ:

6

Объяснение:

\frac{y^{2}-8y+16 }{y^{2}-16 }  : \frac{10y-40}{y^{2}+4y } =\frac{(y-4)(y-4)(y)(y+4) }{(y-4)(y+4)(10)(y-4) }=\frac{60}{10} =6

Похожие вопросы
Предмет: Русский язык, автор: Ирина804
Предмет: Алгебра, автор: MandarinBlin